Dramaturgi: Sebuah Pertunjukkan Panggung Depan Kehidupan Sosial Para Pelaku Awe-Awe Jalur Gumitir, Kabupaten Jember - Febriyanti Alya Janah; Nisrina Husna Alifia; Silvia Lusiani (Lembaga Pengembangan Kinerja Dosen, 2023)
The social phenomenon of awe-awe actors that occurs on the Gumitir route, Garahan Village, Jember Regency. Along the edge of the Gumitir lane, there is a group of residents known as